The Performance of Mangupa Tradition in Angkola Custom, Medan, Indonesia - Akhiril Pane; Robert Sibarani; Ikhwanuddin Nasution; Muhammad Takari (Budapest International Research and Critics University, 2020)
The Angkola oral tradition of mangupa is as household advice by appealing to Allah SWT. This tradition is trusted by indigenous communities to restore the spirit to the body (paulak tondi tu badan). As the object of study is the performance analysis by using Duranti theory (2001: 14) with a view of a) performance, b) indexcality, and c) participation and theory of the performance. Finnegan (1991, 1992: 92-93) states that there are 3 elements such as: a) composition, a form that is composed, b) transmission, the selection process that will continue the oral tradition, and (3) the audience. The methods used are surveys, interviews with key informants, primary data source at the ceremony and secondary data by collecting field data, analyzing data. The result of the analysis of traditional Angkola data is divided into four components: a) Ceremonial place, b) Ceremonial time c) Traditional tools, d) Traditional leaders and participants. The transmission of customary philosophy: sangap, hamomora. and hamoraon. The audiences are all who attended the Angkola traditional wedding ceremony in the tradition of mangupa. The advice on mangupa consists of: 1) mangupa text using the name of Allah SWT, 2) mangupa texts of prayer and hope, 3) mangupa text of hope, and 4) mangupa text with philosophical Angkola custom.